The Indonesia Colorectal Cancer Risk Assessment (Ina_Cocara):Identifikasi Profil Risiko Pada Mahasiswa - Vivop Marti Lengga; R. Siti Jundiah; Sumbara Sumbara (Universitas Malahayati, 2025)
ABSTRACT Colorectal cancer is the third most common type of cancer and the second most common cause of cancer-related deaths worldwide, including Indonesia. The number of colorectal cancer patients diagnosed at a young age is still under-detected, so the risk of death is higher. This impact can be reduced by implementing a primary preventive strategy to determine the level of risk earlier through the latest instrument specifically for the Indonesian community and non-invasive in the form of The Indonesian Colorectal Cancer Risk Assessment (Ina_CoCaRA). This study aims to develop the Ina_CoCaRA nursing assessment instrument, as well as to analyze the risk profile of colorectal cancer incidence in nursing students. This quantitative study uses a descriptive method, to describe the risk profile of colorectal cancer in a group of students through the Ina_CoCaRA assessment instrument which has been tested for validity and reliability. The number of samples was 100 students with a sampling technique using the stratified random sampling technique. The results showed that the risk profile of colorectal cancer in students included no risk (27%) and low risk (73%). This means that most students have a risk, although in the low category, of developing colorectal cancer. This occurs due to lifestyle factors, especially frequent consumption of junk food, lack of exercise, and sedentary lifestyle factors. The risk profile of colorectal cancer in students using the Ina_CoCaRA instrument is low risk. If there is no change in a healthier lifestyle, the risk of developing colorectal cancer with increasing age can be categorized as moderate or even severe. The development of the Ina_CoCaRA instrument is still needed according to the age group and culture of each region to determine early detection instruments that can be given periodically so that colorectal cancer does not occur. Keywords: Colorectal Cancer, Ina_CoCaRA, Risk Assessment, Risk Profile ABSTRAK Kanker kolorektal merupakan jenis kanker terbanyak ketiga dan menjadi penyebab kematian terbanyak kedua terkait kanker di seluruh dunia, termasuk Indonesia. Jumlah pasien kanker kolorektal yang terdiagnosis pada usia muda masih kurang terdeteksi dengan cepat, sehingga risiko kematian menjadi lebih tinggi. Dampak ini dapat dikurangi dengan menerapkan strategi preventif primer untuk mengetahui tingkat risiko lebih dini melalui instrumen terbaru khusus masyarakat Indonesia dan noninvasif berupa The Indonesian Colorectal Cancer Risk Assessment (Ina_CoCaRA). Penelitian ini bertujuan untuk mengembangkan instrumen pengkajian keperawatan Ina_CoCaRA, sekaligus menganalisis profil risiko kejadian kanker kolorektal pada Mahasiswa Universitas Bhakti Kencana. Penelitian kuantitatif ini menggunakan metode deskriptif, untuk menggambarkan profil risiko kanker kolorektal pada kelompok mahasiswa melalui instrumen pengkajian Ina_CoCaRA yang telah teruji validitas dan reliabilitasnya. Jumlah sampel sebanyak 100 mahasiswa dengan teknik pengambilan sampel menggunakan teknik stratified random sampling. Hasil penelitian menunjukkan bahwa profil risiko kanker kolorektal pada mahasiswa meliputi tidak berisiko (27%) dan berisiko rendah (73%). Artinya, sebagian besar mahasiswa memiliki risiko meskipun dalam kategori rendah untuk mengalami kanker kolorektal. Hal ini terjadi karena faktor gaya hidup terutama seringnya mengonsumsi junk food, kurang olahraga, dan faktor sedentary lifestyle. Profil risiko kanker kolorektal pada mahasiswa melalui instrumen Ina_CoCaRA yaitu berisiko rendah. Jika tidak ada perubahan gaya hidup yang lebih sehat, maka risiko terjadinya kanker kolorektal seiring bertambahnya usia dapat menjadi kategori sedang bahkan berat. Masih dibutuhkan pengembangan instrumen Ina_CoCaRA sesuai kelompok usia dan budaya tiap daerah untuk menetapkan instrumen deteksi dini yang dapat diberikan secara berkala sehingga kanker kolorektal tidak terjadi. Kata Kunci: Ina_CoCaRA, Kanker Kolorektal, Profil Risiko, Risk Assessment.